In vitro P-glycoprotein activity of alkaloid-enriched fractions from Solanum aculeastrum and its synergistic potential with doxorubicin - Cordier, Werner (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.